Domesticating whatsApp groups: Indonesian women’s experience with misinformation and hate speech in the 2019 election - Wendratama, Engelbertus; Aprilia, Monika P.; Novi Kurnia,; Wisnu Prasetya Utomo,
There are rising concerns over the spread of misinformation and hate speech on mobile instant messaging, especially during political elections. In 2019, when Indonesia held its legislative and presidential elections, WhatsApp groups had become the main source of the harmful content for Indonesians, with politically motivated content being the most received. This paper examined how Indonesian women used WhatsApp groups and addressed the harmful content on the platform during the arguably most divisive presidential election in the country’s history. Their experiences were approached with the four processes of domestication: appropriation, conversion, incorporation, and objectification. This study applies qualitative approach by conducting semi-structured interviews with 30 informants selected through purposive sampling technique in five Indonesian cities namely Jakarta, Banda Aceh, Yogyakarta, Makassar, and Jayapura. This study found that WhatsApp groups enabled them to gain self-actualization for professional and personal purposes, but their experience was disrupted by the political event that drove misinformation and hate speeches. Based on their gender identity, political interest and ethnicity, they responded to misinformation and hate speech differently in different WhatsApp groups, ranging from ignoring to verifying and debunking them. Their responses to misinformation and hate speech differ depending on their understanding of gender bias, political interests, as well as religious and ethnic identities, which are also influenced by the type of group and conversations on WhatsApp groups.